(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Climate change has emerged as one of the most pressing global challenges, and India’s western state of Gujarat faces distinctive risks due to its semi-arid geography, long coastline, and industrial profile. Non-Governmental Organizations (NGOs) have become crucial actors in bridging local realities with national and global climate policies. This study explores the empirical role of NGOs in mitigating climate change across Gujarat. Drawing upon secondary data from the Gujarat State Action Plan on Climate Change (SAPCC), the Indian Meteorological Department (IMD), and reports from organizations such as SEWA, Vasudha Foundation, and TERI, the paper identifies how NGOs implement renewable energy solutions, afforestation, water conservation, and community-based resilience programs. The findings demonstrate that NGOs not only complement state interventions but also pioneer bottom-up innovations that strengthen climate governance. The study concludes with policy recommendations to institutionalize NGO participation within Gujarat’s climate framework.